Information Disclosure and Consumer Awareness - Sanxi Li; Martin Peitz; Xiaojian Zhao (University of Mannheim, Department of Economics, 2014)
Whether consumers are aware of potentially adverse product effects is key to private and social incentives to disclose information about undesirable product characteristics. In a monopoly model with a mix of aware and unaware consumers, a larger share of unaware consumers makes information disclosure less likely to occur. Since the firm is not interested in releasing information to unaware consumers, a more precise targeting technology that allows the firm to better keep unaware consumers in the dark leads to more disclosure. A regulator may want to intervene in this market and impose mandatory disclosure rules.
urn:nbn:de:bsz:180-madoc-373775
Keywords: L51; M38; 330; Information disclosure; informative advertising; targeted advertising; consumer awareness; behavioral bias; non-common prior; consumer protection; behavioral industrial organization